Classroom Action Research: Improving Student Achievement and Promoting Equity - Ardine, Maria Novia; Nur’Aini, Siti; Wiyaka, Wiyaka (Universitas PGRI Semarang, 2023)
Teaching and learning centers play a vital role in supporting teachers who are seeking to improve their practices or find new strategies to address the challenges in their classrooms. One major dilemma teachers face is selecting the most effective teaching strategies for their specific classroom situations. This challenge is influenced by a variety of factors, including class size, subject matter, student demographics, and the teachers' own skills and teaching styles. As educators strive to meet the diverse needs of their students, finding the right approach can be overwhelming. Classroom Action Research (CAR) provides a systematic way for teachers to explore and address these challenges. Through this process, teachers engage in a cycle of inquiry—planning, acting, observing, and reflecting—allowing them to make informed decisions about their teaching practices. CAR empowers teachers to critically examine their own teaching methods, consider their personal values, and identify strategies that best align with the needs of their students. By working collaboratively, teachers can share insights and refine their practices, creating a collective, evidence-based approach to teaching. This paper discusses the interactive process of CAR, emphasizing its role in helping teachers reflect on their practices, experiment with new strategies, and develop a shared understanding of effective teaching. It highlights how CAR can lead to immediate, meaningful changes in teaching and learning.